2022
DOI: 10.3390/healthcare10020230
|View full text |Cite
|
Sign up to set email alerts
|

A Link between Handgrip Strength and Executive Functioning: A Cross-Sectional Study in Older Adults with Mild Cognitive Impairment and Healthy Controls

Abstract: Older adults with amnestic mild cognitive impairment (aMCI) who in addition to their memory deficits also suffer from frontal-executive dysfunctions have a higher risk of developing dementia later in their lives than older adults with aMCI without executive deficits and older adults with non-amnestic MCI (naMCI). Handgrip strength (HGS) is also correlated with the risk of cognitive decline in the elderly. Hence, the current study aimed to investigate the associations between HGS and executive functioning in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 106 publications
(174 reference statements)
1
4
0
Order By: Relevance
“…HGS could be one of the indicators for cognitive impairment. HGS was found to be associated with cognition especially in executive function tasks [55][56][57]. Our study found that the association between cognitive function and TUG was consistent with previous studies [58][59][60].…”
Section: Discussionsupporting
confidence: 92%
“…HGS could be one of the indicators for cognitive impairment. HGS was found to be associated with cognition especially in executive function tasks [55][56][57]. Our study found that the association between cognitive function and TUG was consistent with previous studies [58][59][60].…”
Section: Discussionsupporting
confidence: 92%
“…Stronger grip strength in patients with amnestic mild cognitive impairment (MCI) was related to better executive function, possibly due to changes in the hippocampus-prefrontal network integrity. 28 This study found that AD-LGS patients had extensive micro-and macrostructural changes in WM fiber tracts, accompanied by extensive cognitive decline, suggesting that changes in specific WM fiber pathways in AD patients may link cognitive decline and reduced grip strength. AD is characterized by large-scale brain network dysfunction associated with Aβ deposition, neurofibrillary tangles, cortical atrophy, and functional disconnection between cortical areas.…”
Section: Discussionmentioning
confidence: 57%
“…However, their glycaemic status was unknown [ 44 ]. On the other hand, Herold et al (2022) [ 45 ] found that HGS may be associated with executive functioning, especially in amnestic type MCI, possibly due to neural connectivity in addition to differences in prefrontal cortex hemodynamic and frontal cortical thinning [ 45 ].…”
Section: Discussionmentioning
confidence: 99%